PENERAPAN FORCE MAJURE DALAM PERJANJIAN ANGKUTAN LAUT ANTARA PT. PELAYARAN KURNIA SAMUDRA DAN PT. ANCARA LOGISTICS INDONESIA - Rahayu Silvia Annisa; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In sea transportation agreements, there are no escape from disputes such as whatoccurred in the agreement between PT. Pelayaran Kurnia Samudra and PT.Ancara Logistics Indonesia. In the implementation of the agreement, a forcemajeure event occurred which resulted in the fulfilment of achievements beinghampered by PT. Pelayaran Kurnia Samudra. Therefore, the purpose of writingthe thesis is first, to find out the application of force majeure in the study seatransportation agreement between PT. Pelayaran Kurnia Samudra and PT.Ancara Logistics Indonesia. Second, to find out the legal rules in determiningforce majeure in the sea transportation agreement between PT. Pelayaran KurniaSamudra and PT. Ancara Logistics Indonesia.This type of research classified as a type of sociological juridical research. Thelocation located in the office of PT. Pelayaran Kurnia Samudra in Batam City,while the population and sample are all parties related to the problem understudy. This study uses data sources in the form of primary data and secondarydata, and data collection techniques are carried out by interviews.There are two main things that can be concluded. First, the non- fulfillment offorce majeure elements by PT. Pelayaran Kurnia Samudra caused them to have topay for the late delivery of goods due to a lack of sufficient evidence to convincePT. Ancara Logistics Indonesia that there has been a force majeure. Second, todetermine force majeure events, Article 41Paragraph 2 of Law Number 17 of2008 Concerning Shipping can be used a reference that can be used by theparties. The author's suggestion is: Firstly, the parties should pay attention to theimportance of including a force majeure clause clearly in the agreement tominimize losses borne by the parties if a force majeure event occurs. Second, it isrecommended that the government include special provisions governing forcemajeure so that it can be used as reference to protect the interests of the parties sothat there is a balance in the severity of responsibilities and rights.Keywords: Force Majeure – Agreement – Ocean Freight